(untitled) (JOSAR (Journal of Students Academic Research), 2025)
This study examines the effect of board characteristics such as gender, age, education and board experience on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. This study aims to understand how these factors shape corporate financial decisions, especially when deciding on the composition of equity and debt capital. The research method used is based on a quantitative approach with regression analysis techniques. This technique is used to analyze the relationship between the independent variables (gender, age, education and board experience) with the dependent variable (capital structure) and company size as a control variable. The data used is taken from the annual reports of manufacturing companies listed on the IDX for 2021 to 2023. The results show that the age and experience of board members have a significant influence on capital structure, while gender and education have no influence. The results of this study provide new insights for management to develop an ideal financial strategy based on the leadership characteristics of the board of directors. Investors, shareholders and regulators can use the results of this study to assess leadership factors that have a potential impact on corporate financial policy. In addition, this study contains suggestions for further research that may include deepening the analysis in other industries or expanding the variables analyzed.